Characterization of Thermally Evaporated In2S3 Films for Solar Cell Application. (27th May 2013) - Ramya, K.; Reddy, M. V.; Ramakrishna Reddy, K. T.
Abstract : Indium sulphide (In2 S3 ) is one of the best alternatives for CdS as a buffer layer in CuInGaSe2 -based thin film heterojunction solar cells. In this work, In2 S3 films were prepared by thermal evaporation of In2 S3 powder onto glass substrates at different temperatures that vary from 200°C to 300°C. The as-grown films were characterized using appropriate techniques to evaluate the chemical and physical properties. The X-ray diffraction analysis revealed that all the films were polycrystalline in nature with a strong (109) plane as the preferred orientation and consisted of tetragonal and cubic phases. The crystallite size and the lattice parameters are calculated. The scanning electron micrographs indicated smooth surface with fine grains. The optical analysis revealed a high optical transmittance for the layers with a direct optical band gap that varied in the range of 1.8–2.2 eV.